Intergenerational Downward Mobility in Educational Attainment and Occupational Careers in West Germany in the Twentieth Century - Martin Diewald; Wiebke Schulz; Tina Baier (European Sociological Review, 2015)
What happens in the occupational careers of men if the intergenerational continuity in status reproduction is disrupted by the failure to reproduce the parental level of educational attainment? We frame this failure as a risk for intergenerational status maintenance and ask whether such a risk induces extra effort by way of compensation. By studying eight birth cohorts born between 1919 and 1971 characterized by largely differing conditions with regard to educational and occupational opportunities, we examine how macro-social conditions contribute to opportunities to compensate for such failure later on. In examining this question, we add a new piece to the puzzle of how social origin and education contribute to status attainment and of how the social context shapes these linkages across historical time. We estimated multilevel growth curve models to assess the effect of educational downward mobility on the development of occupational status over the career. Our empirical results show that the status of men who experience educational downward mobility increases faster over the course of their careers. Moreover, these men reach a slightly higher status as compared to their peers who had reached at least the same educational level as their fathers. The prevailing macro-societal conditions did not cause variation in the effect of educational downward mobility on men's career attainment.
Additional information: This is a pre-copy-editing, author-produced PDF of an article accepted for publication in “European Sociological Review” following peer review. The definitive publisher-authenticated version "Intergenerational Downward Mobility in Educational Attainment and Occupational Careers in West Germany in the Twentieth Century / Martin Diewald, Wiebke Schulz, Tina Baier. In: European Sociological Review 31 (2015), 2, 172-183" is available online at: http://dx.doi.org/10.1093/esr/jcv010
Keywords: 330